L’hybridité entre la musique et l’image au cinéma : la question du support - Violaine Anger (Itinéraires)
This article compares three artworks marked by abstraction, and by their exploration of the link between music and image : some watercolors by Paul Klee, still images imbued with a reflection on time; Bach's Toccata and Fugue in Walt Disney's version of Fantasia; Trama by Christian Lebrat. The notion of hybridity seems relevant for Klee, hardly relevant for Disney and undoubtedly relevant for Lebrat, but only because of the object is different: Lebrat works on film while Klee works on the medium as a place that welcomes a directionless energy, lines and colors. Disney, focused on the issue of synchronisation, sidesteps these issues, and prefers to stay within the framework of representation and imitation. This comparison therefore makes it possible to clarify one of the major issues at stake in the notion of hybridity, that of the medium, and to understand that it involves, in fact, a semiology.